Toward Decoding Bioelectric Events in Xenopus Embryogenesis: New Methodology for Tracking Interplay Between Calcium and Resting Potentials In Vivo. Issue 2 (17th January 2020) - McMillen, Patrick; Novak, Richard; Levin, Michael
Abstract: Although chemical signaling during embryogenesis is readily addressed by a plethora of available techniques, the developmental functions of ionic signaling are still poorly understood. It is increasingly realized that bioelectric events in nonneural cells are critical for pattern regulation, but their study has been hampered by difficulties in monitoring and manipulating them in vivo . Recent developments in visualizing electrical signaling dynamics in the field of neuroscience have facilitated functional experiments that reveal instructive developmental bioelectric signals. However, there is a pressing need for additional tools to explore time-dependent ionic signaling to understand complex endogenous dynamics. Here, we present methodological advances, including 4D imaging and data analysis, for improved tracking of calcium flux in the Xenopus laevis embryo, lowering the barrier for in vivo physiology work in this important model system. Using these techniques, we investigated the relationship between bioelectric ion channel activity and calcium, finding that cell hyperpolarization and depolarization both induce persistent static elevation of cytoplasmic calcium levels that fade over developmental time. These calcium changes correlate with increased cell mobility in early embryos and abnormal craniofacial morphology in later embryos. We thus highlight membrane potential modulation as a tractable tool for modulation of signaling cascades that rely on calcium as a transduction mechanism. The methods we describe facilitate the study of important novel aspects of developmental physiology, are extendable to numerous classes of existing and forthcoming fluorescent physiological reporters, and establish highly accessible, inexpensive protocols for their investigation. Graphical abstract: Image 1 Highlights: Advances in physiological imaging are critical for advancing developmental biology. A novel mold design enables upright time-lapse imaging in Xenopus embryos. Imaging workflow representing 3D structures in 2D enables bioelectric profiling. Changing resting potential via ion channel mRNA induces persistent Ca 2+ signals. Bioelectric manipulation induces hypermigration of high-calcium cells.